Health Pass in France – The Ethics of Conviction and the Ethics of Responsibility - Ljiljana Čabrilo Blagojević (International Society of Philosophy and Cosmology, 2021)
The arrival of COVID-19 marks the return of the state. In this pandemic anomie, institutions are facing challenges to which they are struggling to find adequate answers. How to juggle between the need for general protection imposed by the health crisis and the individual rights so dear to democracies? How to strike a balance between protection and deprivation, between coercion and conviction of the correctness of decisions? In search of the best solutions, the state wanders, often adopting an overly paternalistic attitude, which irritates the population. But indecision in management, especially in times of crisis, can do even more damage.